Experimental Measurement and Simulation of Railway Track Irregularities - L. Bouhlal; N. Lamdouar; F. Kassou (Salehan Institute of Higher Education, 2022)
The study of railway dynamics is still a productive area of research given the rapid technological evolution of this transport system regarding load and speed. Morocco is no exception to this rule, especially after the commissioning of the first high-speed line in Africa. This study describes herein an experiment to measure vertical and transverse accelerations in a locomotive on a railroad line connecting the two cities of Mchraa Ben Abbou and Marrakech. The observed accelerations constitute the vehicle's dynamic responses while running at a constant speed on a track with irregularities (also known as track geometry), which is considered the main driving force of train dynamics and the track system. They are used to evaluate passenger comfort and safety. It can also be observed that body accelerations increase with the introduction of track irregularities as compared to a smoother track. In this study, an analysis of these experimental measurements is performed based on boxplot simulations comparing the distributions of the transverse and vertical components of vehicle acceleration. It was found that the medians and first and third quartiles of both distributions are very close. Doi: 10.28991/CEJ-2022-08-10-014 Full Text: PDF